miR-221-5p-Mediated Downregulation of JNK2 Aggravates Acute Lung Injury - Yang, Jing; Do-Umehara, Hanh Chi; Zhang, Qiao; Wang, Huashan; Hou, Changchun; Dong, Huali; Perez, Edith A.; Sala, Marc A.; Anekalla, Kishore R.; Walter, James M.; Liu, Shuwen; Wunderink, Richard G.; et al. (Frontiers in Immunology, 2021)
The two ubiquitously expressed and highly homologous isoforms of c-Jun N-terminal protein kinase (JNK), JNK1 and JNK2, exhibit overlapping but also distinct biological functions. We previously reported that JNK2, but not JNK1, promotes stress-induced mitophagy by targeting small mitochondrial ARF for ubiquitin-mediated proteasomal degradation, thereby preventing mitochondrial dysfunction. Here we report that loss of JNK2 exacerbates lung inflammation and injury during sepsis in mice. JNK2 is downregulated in septic mice, concomitantly correlated inversely with disease severity. MicroRNA sequencing revealed that miR-221-5p, which contain seed sequence matching to JNK2 mRNA 3’ untranslated region and are upregulated with dynamically inverse correlation with JNK2 mRNA levels in response to lipopolysaccharides, targets JNK2 mRNA for destruction. Importantly, in patients with pneumonia in medical intensive care unit, JNK2 mRNA levels in alveolar macrophages flow sorted from non-bronchoscopic broncholaveolar lavage (BAL) fluid were inversely correlated strongly and significantly with the percentage of neutrophils, neutrophil and white blood cell counts in BAL fluid. Our data provide a potential mechanism for the well-documented association between mitochondrial dysfunction and sepsis.